A computational study of droplet-spray formation from pressurized metered dose inhalers with applications to drug deposition in a human lung-airway model. Issue 5 (4th May 2023) - Sridhar, Karthik; Chari, Sriram; Kleinstreuer, Clement
Abstract: Orally administered drugs using portable devices, such as pressurized metered dose inhalers (pMDIs), can alleviate the symptoms of various respiratory diseases. The basic non-isothermal fluid-particle dynamics of pMDIs have been simulated, including computer model validations and different inhalation techniques, using the Ventolin HFA from GlaxoSmithKline (UK) as a representative application. Specifically, the evolution of thermal droplet sprays has been realistically simulated and experimentally validated, employing the open-source computational fluid dynamics (CFD) toolbox OpenFOAM. The segmental droplet temperature results show elevated temperatures for higher inhalation flow rates because of stronger convective flow around the evaporating droplets. The general problems of high, wasteful oropharyngeal deposition and cold impacting droplets were tackled by devising a new 'pulsed injection' strategy in which the spray was broken into pulses with a time delay between them. This new methodology indicated up to a 20% increase in useful lung deposition beyond the oropharynx over conventional drug administration methods. In addition, compared to the conventional single injection approach, the segmental variations in temperature of the deposited aerosols show an increase in temperature of around 10% and 7% for the 30 LPM and 60 LPM cases up to segment 4 for pulsed injection. An increase of 23% and 13% for the 30 LPM and 60 LPM cases were observed for segments 5–7 for pulsed injection. Also, a reduction in inertia of the droplets at 30 LPM, where the spray was broken into eight pulses with 100 ms delay between them, resulted in higher residence times and an increase in temperature of over 35 ° C . Copyright © 2023 American Association for Aerosol Research